Pervasive structural racism in environmental epidemiology - Melissa J. Perry; Suzanne Arrington; Marlaina S. Freisthler; Ifeoma N. Ibe; Nathan L. McCray; Laura M. Neumann; Patrick Tajanlangit; Brenda M. Trejo Rosas (BMC, 2021)
Abstract Background Epistemological biases in environmental epidemiology prevent the full understanding of how racism's societal impacts directly influence health outcomes. With the ability to focus on "place" and the totality of environmental exposures, environmental epidemiologists have an important opportunity to advance the field by proactively investigating the structural racist forces that drive disparities in health. Objective This commentary illustrates how environmental epidemiology has ignored racism for too long. Some examples from environmental health and male infertility are used to illustrate how failing to address racism neglects the health of entire populations. Discussion While research on environmental justice has attended to the structural sources of environmental racism, this work has not been fully integrated into the mainstream of environmental epidemiology. Epidemiology's dominant paradigm that reduces race to a mere data point avoids the social dimensions of health and thus fails to improve population health for all. Failing to include populations who are Black, Indigenous, and people of color (BIPOC) in health research means researchers actually know very little about the effect of environmental contaminants on a range of population health outcomes. This commentary offers different practical solutions, such as naming racism in research, including BIPOC in leadership positions, mandating requirements for discussing "race", conducting far more holistic analyses, increasing community participation in research, and improving racism training, to address the myriad of ways in which structural racism permeates environmental epidemiology questions, methods, results and impacts.